Thermo-hydraulic properties of a transverse-jet in a crossflow channel using nanofluids - Kok, Besir (Pergamon-Elsevier Science Ltd, 2020)
Thermophysically developed nanofluids have emerged in many industrial applications in recent years. In this study, flow and thermal mixing behaviors of nanofluids at different temperatures were analyzed. For this purpose, a crossflow channel with a transverse-jet is modeled in which is exemplified in many industrial applications. In the analyzes, two types of nanofluids with Al2O3 and CuO nanoparticles were evaluated compared with water. In addition, different rates of nanoparticles were added to nanofluids and their thermophysical effects were discussed. Temperature difference and momentum ratios between crossflow and the jet flow are also secondary parameters of the study. The results show that the use of nanofluid can improve the thermal mixing performance in industrial mechanisms. An increase in the amount of nanoparticles in the nanofluids did not have a significant effect on the thermal and flow behaviors of the flow.
Keywords: Transverse jet; Crossflow; Thermal mixing; LES; Nanofluids